2016
DOI: 10.3389/fphar.2016.00072
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Effects of α-Asarone on Immobility in the Tail Suspension Test: Evidence for the Involvement of the Noradrenergic and Serotonergic Systems in Its Antidepressant-Like Activity

Abstract: Alpha (α)-asarone is one of the main psychoactive compounds, present in Acorus species. Evidence suggests that the α-asarone possess an antidepressant-like activity in mice. However, the exact dose-dependent effect of α-asarone and mechanism(s) involved in the antidepressant-like activity are not clear. The present study aimed to investigate the dose-dependent effect of α-asarone and the underlining mechanism(s) involved in the antidepressant-like activity of α-asarone in the mouse model of tail suspension tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
(55 reference statements)
2
17
0
Order By: Relevance
“…Asarone derivatives including α- and β-asarone are major bioactive phytochemicals present in the Acorus species such as Acorus calamus Linn and Acorus gramineus Solander [32,33], and Guatteria gaumeri Greenman [34]. The wide range of pharmacological activities of asarone derivatives have been reported including antiepileptic [35], antidepressant [36], anxiolytic [37], neuroprotective [38], and hypolipidemic activities [39]. Numerous clinical studies in China had reported that asarone derivatives were effective therapeutic approaches for the treatment of respiratory disorders and epilepsy [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Asarone derivatives including α- and β-asarone are major bioactive phytochemicals present in the Acorus species such as Acorus calamus Linn and Acorus gramineus Solander [32,33], and Guatteria gaumeri Greenman [34]. The wide range of pharmacological activities of asarone derivatives have been reported including antiepileptic [35], antidepressant [36], anxiolytic [37], neuroprotective [38], and hypolipidemic activities [39]. Numerous clinical studies in China had reported that asarone derivatives were effective therapeutic approaches for the treatment of respiratory disorders and epilepsy [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…and depressive-like activity was seen at relatively higher doses (50 and 100 mg/kg, i.p.) [ 3 ]. Similarly, acute oral administration of a methanolic extract of Mitragyna speciosa leaf (MMS; 50–500 mg/kg) showed an inverted bell-shaped dose response in apomorphine-induced cage climbing behavior in mice [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…and a depressive-like effect at higher doses (≥50 mg/kg, i.p.) [ 186 ]. The antidepressant effect of α-asarone was mediated by its interaction with the noradrenergic (α1 and α2 adrenoceptors) and serotonergic (5-HT1A receptors) systems, whereas the depressive-like effects observed following the administration of high levels of α-asarone may be mediated by interactions with the GABAergic system [ 186 ].…”
Section: Neuroprotective Effects Of α- and β-Asarone On Other Neurolo...mentioning
confidence: 99%
“…[ 186 ]. The antidepressant effect of α-asarone was mediated by its interaction with the noradrenergic (α1 and α2 adrenoceptors) and serotonergic (5-HT1A receptors) systems, whereas the depressive-like effects observed following the administration of high levels of α-asarone may be mediated by interactions with the GABAergic system [ 186 ]. In another study, α-asarone showed an anxiolytic effect in animal models of anxiety, as assessed by the elevated plus-maze, the light–dark transition test, the novel food consumption test, and the marble-burying test [ 187 ].…”
Section: Neuroprotective Effects Of α- and β-Asarone On Other Neurolo...mentioning
confidence: 99%